Rufus Wainwright [entrevista]: Geni i figura - Broc, David (Benzina: Revista d'excepcions culturals, 2007)

Keeping Time with Lesbians on Ecstasy - Halberstam, J[ack] (Women and Music: A Journal of Gender and Culture, 2007)

A Queer Protocol of Homage: Chambres de Ténèbres/Tombeau de Claude Vivier By Marko Nikodijević - Novak, Jelena (International Journal of Music New Sound, 2007)
The music of Canadian composer Claude Vivier (1948-1983) was used as a fractalized material for the creation of the composition Chambres de ténèbres/tombeau de Claude Vivier (2005) by Marko Nikodijević. Vivier’s opus and his marginal queer acting were the pillars of Nikodijević’s meticulous reading/deconstructing of Vivier’s world through his own artistic dilemmas.

Rufus Wainwright. Interview by Paul Zollo - Zollo, Paul (Song: the World’s Best Songwriters on Creating the Music that Moves Us, 2007)
Song is an enthralling compilation of songwriting wisdom from 100 of the biggest names in music. From country to rock to folk to alternative, this genre-spanning collection of interviews captures the anecdotes, history, and wisdom of the best songwriters around - in their words. An entertaining read as well as an indispensable guide to the art and craft of songwriting, Song is a must-have resource for the aspiring, amateur, or professional musician. Inside, you'll find entertaining and enlightening interviews from great songwriters such as Smokey Robinson, Willie Nelson, Jewel, Kenny Chesney, Cat Stevens, Jack Johnson, Sheryl Crow, John Legend, John Mellencamp, Ray Charles, Clint Black, Rob Thomas, Dolly Parton, Rufus Wainwright, Bob McDill, Lyle Lovett, Keith Urban, Beck, M. Ward, Lou Reed, Roger Miller, Grant-Lee Phillips, and John Denver.